Quilted Selves and Shadowed Psyches: A Psychoanalytic Study of Grace Marks - Chandan, Surabhi (International Journal of Humanities and Education Development (IJHED), 2025)
This paper examines Margaret Atwood’s Alias Grace through Freudian and post-Freudian psychoanalytic frameworks, focusing on the psychological complexity of Grace Marks, a historical figure convicted of murder in 19th-century Canada. The novel’s fragmented narrative, recurring motifs, and symbolic textures create a rich terrain for exploring themes of repression, trauma, and identity. Grace’s disjointed memory and ambiguous role in the murders are interpreted as signs of deep psychological distress, particularly tied to the repression of sexual trauma and loss. Drawing from Freud’s concepts of the unconscious, hysteria, and the death drive, as well as post-Freudian ideas on dissociation and trauma narratives, the paper argues that Grace’s psyche functions as a quilted self—stitched together by fragments of repressed memories, alter egos, and symbolic dream language. The novel also interrogates the patriarchal structures of medicine and psychiatry through Grace’s interactions with Dr. Simon Jordan, whose clinical gaze and erotic transference reflect both the objectification of female hysterics and his own unresolved Oedipal conflicts. Symbols such as quilts, mirrors, fruit, and locked rooms serve as unconscious signifiers, revealing buried desires and traumas. Rather than offering a conclusive psychological diagnosis, Atwood resists closure, constructing Grace as a fluid, unstable subject whose multiplicity challenges dominant narratives of truth, guilt, and sanity. Ultimately, Alias Grace becomes both a critique of 19th-century psychiatric discourse and a postmodern meditation on the unknowability of the human mind.